The legal treatment of the skills of police intervention: use of the force and criminal responsibility (2014)
The legitimate use of force by States and the law enforcement means that police represent, usually lacks an adequate regulation. The physical and armed interventions undertaken by police forces are governed by a series of abstract principles embedded in v